Academic Self-Concept and Academic Achievement among University Students - Matovu, Musa (International Online Journal of Educational Sciences, 2012)
The purpose this study was to investigate academic self-concept and academic achievement among university students. The academic self-concept information among university students was collected using the Liu and Wang (2005) academic self-concept scale which was composed of two sub-scales; academic confidence and academic effort scales. The study was conducted on 394 university students; males and females from different levels of study and faculties in a public university in Malaysia. MANOVA was used to analyse the collected data and the results revealed that there was a statistically significant effect of gender on academic effort and academic achievement, while also a statistically significant difference was shown in faculties on academic achievement. Again a difference was noted in the interaction between gender, faculties, and levels of study on academic achievement. The Post Hoc results indicated that a statistically significant difference existed in between the faculties Arts and Human Sciences.
Keywords: Academic Self-Concept; Academic Achievement; University Students